Pengaruh Pijat Oksitosin Menggunakan Minyak Lavender Terhadap Kecukupan ASI Pada Ibu Menyusui di Wilayah Kerja Puskesmas Bintang Ara - Dewi, Mia Novita; Rahmawati, Dwi; Ulfa, Ika Mardiatul (Pusat Riset dan Inovasi Nasional, 2024)
Exclusive breastfeeding coverage at Bintang Ara Health Center in 2019 reached 69%, while in 2020 exclusive breastfeeding coverage was 61% and in 2021 exclusive breastfeeding coverage was 57.83%. This is still far from the target of 80%. This problem can be overcome by giving a complementary therapy, namely through oxytocin massage. The purpose of the study was to determine the effect of oxytocin massage using lavender oil on the adequacy of breast milk in breastfeeding mothers in the Bintang Ara Health Center Work Area. The research method uses a type of research that is Quasy Experimental Pre test- Posttest Control Group Design. With a case sample of 8 people and a control sample of 8 people. Statistical tests using the Wilcoxon test. The results of the study that before the intervention of oxytocin massage using lavender oil, the adequacy of breast milk was less and increased after the intervention. Wilcoxon test results obtained p-value less than α which is 0.008<0.005.